Optical properties of calcium aluminate phosphors - Ziyauddin, Mohammad; Brahme, Nameeta; Bisen, D P; Kher, R S (Recent Research in Science and Technology, 2012)
Thermoluminescence properties of CaAl2O4 was studied. It was found that firstly the TL intensity increases with increase in UV irradiation time and it attains a maximum value for 20 minute irradiation time. TL intensity decreases with further increase in irradiation time.